¿Disposable Matter or Personal Entity? The Human Body, Biotechnology and the Juridical Requirements of Dignity - Jorge Nicolás Lafferriere (Sociología y Tecnociencia, 2018)
Biotechnological interventions affect the human body in new and powerful ways in the process of procreation, through actions of enhancement or replacement of the body, or by the search of the immortality of the body. This implies new legal challenges to prevent biotechnoscience from considering the human body as "operable and disposable matter", and treating it as the human person himself. In this article, we will study these challenges, starting from human dignity as a fundamental principle for an assessment of this biotechnology, and focusing on four legal issues: improvement interventions and their legal enforceability; the commodification of human life; growing social inequalities and the emergence of new forms of discrimination; and the principle of integrity of the human species.